2018
DOI: 10.1158/0008-5472.can-18-1477
|View full text |Cite
|
Sign up to set email alerts
|

Development, Function, and Clinical Significance of Plasmacytoid Dendritic Cells in Chronic Myeloid Leukemia

Abstract: Plasmacytoid dendritic cells (pDC) are the main producers of a key T-cell-stimulatory cytokine, IFNα, and critical regulators of antiviral immunity. Chronic myeloid leukemia (CML) is caused by BCR-ABL, which is an oncogenic tyrosine kinase that can be effectively inhibited with ABL-selective tyrosine kinase inhibitors (TKI). BCR-ABL-induced suppression of the transcription factor interferon regulatory factor 8 was previously proposed to block pDC development and compromise immune surveillance in CML. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Immunologic mechanisms are often invoked but, at present, they remain hypothetical [ 59 , 60 , 61 ]. Some evidence on a specific role of lymphocyte sub populations (NK) has been reported, but deeper studies of the immunologic mechanisms in CML patients during TKI treatment should be addressed [ 62 , 63 ]. Combinations of TKIs with other drugs having different mechanisms of action should be tested, even if no new effective molecules with this potential are currently available and, in any case, the combinations tested “in vitro” must be safe “in vivo”.…”
mentioning
confidence: 99%
“…Immunologic mechanisms are often invoked but, at present, they remain hypothetical [ 59 , 60 , 61 ]. Some evidence on a specific role of lymphocyte sub populations (NK) has been reported, but deeper studies of the immunologic mechanisms in CML patients during TKI treatment should be addressed [ 62 , 63 ]. Combinations of TKIs with other drugs having different mechanisms of action should be tested, even if no new effective molecules with this potential are currently available and, in any case, the combinations tested “in vitro” must be safe “in vivo”.…”
mentioning
confidence: 99%
“…For example, immuno-biological features such as CD86 + plasmacytoid dendritic cell counts were recently shown to be associated with both TFR rate and rapid, deep MR under TKI therapy. 31,32…”
Section: Discussionmentioning
confidence: 99%
“… 77 , 81 , 82 Conversely, immune suppressor cells such as regulatory T-cells (Tregs) and myeloid-derived suppressor cells (MDSCs) expand during disease progression or relapse and are reduced following TKI therapy. 77 , 80 Other immunological factors, such as dendritic cells (DCs), 83 plasmacytoid dendritic cells (pDCs), 84 CD8 + cytotoxic T-cells (CTLs), 85 leukemia-associated antigens (LAAs), 86 and B-cells, 87 also play a pivotal role in contributing to CML; however, further investigation should be launched to explore their impact on therapy responses. Additionally, studies have also indicated that imatinib and dasatinib treatment generates a more active immune system, and changes were not observed during bosutinib treatment.…”
Section: What Is a Better Methods Of Management?mentioning
confidence: 99%